KEBEBASAN BERAGAMA PERSPEKTIF HAK ASASI MANUSIA - I WAYAN PUSPA; I MADE SURADANA; SYAIFULLAH SYAIFULLAH; TRI LAKSONO KURNIAWAN; MUHAMMAD IKBAL (Universitas Mahasaraswati K. Mataram, 2023)
Violations of freedom of religion and worship often occur among the community. If this is allowed to happen, it is feared that it could lead to divisions that lead to the disintegration of the nation. The problem is: